Translating John Dewey's Idea of Education as a Social Function into EFL Teaching Practices - Ahmad, Zuhad; Ilyas, Hamzah Puadi (Universitas Pahlawan Tuanku Tambusai, 2026)
This article represents the writers’ independent perspectives regarding the conversion of John Dewey’s ideas about education as a social function. As is recognized, Dewey’s philosophical vision of education has been embraced by educational authorities in numerous countries, and his ideas remain pertinent in the contemporary era, where the intricacies of societal challenges converge with the advancement of technology. The world appears to be becoming increasingly interconnected. In the context of EFL, students must be equipped with the tools to effectively process the rapid influx of information and actively engage in societal issues to address challenges. Accordingly, this article aims to translate Dewey’s concept of education as a social function, given that there is still a paucity of literature on this topic, despite the prevalence of studies that indirectly utilize Deweyan ideas, such as collaborative learning. However, no explicit connection is made to Dewey’s ideas in education. This article commences with an examination of Dewey's education as a social function, subsequently extending the analysis to the context of EFL instruction. In this section, the writers propose EFL teaching instructions and activities that align with the tenets of Deweyan philosophy. It is hoped that this article will contribute to the ongoing discourse on the interconnection between EFL and the social function of education and provide insights for EFL educators in the formulation of instructional strategies, given the dual objective of equipping learners with linguistic proficiency and preparing them to take responsible roles within their communities.